Republic of Kosovo: 2015 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Republic of Kosovo (IMF Staff Country Reports: Country Report No. 15 / 131, 2015)
KEY ISSUES Context: Following a six-month political stalemate, the largest two parties reached an agreement in December to form a grand coalition, which enjoys a comfortable majority in parliament. The remittances-fueled growth is set to continue in the near term, but deep challenges remain in view of Kosovo's narrow export and productive base, low employment ratios, and incomes that are among the lowest in Europe. Fiscal Policy: Following very generous pre-electoral promises, gradual fiscal adjustment is required to preserve the credibility of the fiscal rule and safeguard low public debt levels. Measures should focus on arresting the rapid growth in unproductive current spending, so as to reduce the deficit while creating space for priority areas such as infrastructure, education, and health. Financial Sector: The banking sector has remained well-capitalized, liquid, and profitable.